Comparison of biochar, zeolite and their mixture amendment for aiding organic matter transformation and nitrogen conservation during pig manure composting. (December 2017) - Wang, Quan; Awasthi, Mukesh Kumar; Ren, Xiuna; Zhao, Junchao; Li, Ronghua; Wang, Zhen; Chen, Hongyu; Wang, Meijing; Zhang, Zengqiang
Highlights: Mixture of additives was compared with biochar and zeolite blended PM composting. Biochar + zeolite amendment reduced NH3 (63.40%) and N2 O (78.13%) emissions. Biochar + zeolite could improve organic matter degradation and humification. Biochar + zeolite addition improved the compost quality. Biochar + zeolite addition reduced the maximum mobility of Cu and Zn. Abstract: The aim of this work was to compare the impact of biochar, zeolite and their mixture on nitrogen conservation and organic matter transformation during pig manure (PM) composting. Four treatments were set-up from PM mixed with wheat straw and then applied 10% biochar (B), 10% zeolite (Z) and 10% biochar + 10% zeolite (B + Z) into composting mixtures (dry weight basis), while treatment without additives applied used as control. Results indicated that adding B, Z and B + Z could obviously ( p  < 0.05) improve the organic matter degradation and decrease the nitrogen loss. And combined addition of B and Z further promoted the organic matter humification and reduced the heavy metals mobility. Meanwhile the highest mitigation of ammonia (63.40%) and nitrogen dioxide (78.13%) emissions was observed in B + Z added treatment. Comparison of organic matter transformation, nitrogen conservation and compost quality indicated that the combined use of biochar and zeolite could be more useful for PM composting.